(untitled) (Journal of Geography and Environmental Management, 2025)
This article is devoted to the study of the processes of economic integration in various sectors of national economies of the border regions of Northern Kazakhstan and the subjects of the Russian Federation bordering them. This direction is particularly relevant at the present stage of socio-economic and political development of our country, since the current geopolitical and geo-economic situation in the post-Soviet space requires an assessment of the effectiveness and rethinking of the processes of economic integration of the border regions in order to choose the most optimal path for further development. In this regard, this article attempts an economic and geographical analysis of the economic integration of Kostanay, Pavlodar and North Kazakhstan regions with neighboring regions of Russia, during which a summary score assessment of the degree of economic integration was made using calculations of various economic and geographical indicators. The system of integration indicators includes macroeconomic and economic-geographical parameters, which were calculated on the basis of statistical materials. Since the parameters used are not always comparable, and also due to the fact that there may be a different trend for each parameter, points were assigned to the obtained values of the studied parameters for the final assessment of the level of economic integration. The main result of this work was the ranking of the border regions of Northern Kazakhstan by the level of economic integration and the compilation of a map of a summary score assessment of the degree of economic integration using GIS technologies.